2005
DOI: 10.2136/sssaj2004.0282
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Gross Nitrogen Transformations and Nitrogen Retention in Grassland Soils Using FLUAZ

Abstract: The flux of N through mineralization–immobilization turnover (MIT) in grassland soils is a major determinant for plant N uptake and for N loss processes. In this study we investigated the dynamics of gross N transformation rates and potential N retention on mineral fertilizer addition in three permanent grassland soils of varying texture (loamy sand, loam, and clay loam). Gross N transformation rates were calculated with the 15N‐tracing model FLUAZ. Differentially 15N‐labeled NH4NO3 (at a rate of 100 mg N kg−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
2
8
1
Order By: Relevance
“…In the four soils studied, the gross NH 4 + immobilization rates in the first day after addition of the NH 4 NO 3 solution were considerably higher than those in the rest of the incubation, consistent with the result of Accoe et al (2005). The large amount of NH 4 + -N added to the soil might have stimulated NH 4 + immobilization.…”
Section: Discussionsupporting
confidence: 80%
“…In the four soils studied, the gross NH 4 + immobilization rates in the first day after addition of the NH 4 NO 3 solution were considerably higher than those in the rest of the incubation, consistent with the result of Accoe et al (2005). The large amount of NH 4 + -N added to the soil might have stimulated NH 4 + immobilization.…”
Section: Discussionsupporting
confidence: 80%
“…This is confirmed by the finding that also for the forest floor SOC content as well as C/N ratio are higher at the warm-dry SW site as compared to the other sites characterized by cool-moist microclimate (Dannenmann et al 2006). Accoe et al (2004) reported ratios of gross N immobilization to gross N mineralization in grassland soils to increase with increasing C availability and Accoe et al (2005) related differences in the relative N retention across three grassland soils to different soil C content. Both studies concluded that potential N retention in soils through microbial N immobilization tends to be limited by C availability.…”
Section: Thinning Effects On Microbial Biomasssupporting
confidence: 65%
“…1c) may restrict heterotrophic NO 3 − utilization (Booth et al 2005;Dannenmann et al 2006). Second, it may alter the competitive balance of microbial NH 4 + utilization in favor of autotrophic nitrification and at the expense of heterotrophic microorganisms performing N immobilization (Accoe et al 2004(Accoe et al , 2005Booth et al 2005;Dannenmann et al 2006). This indirect effect of C availability on autotrophic nitrification could have been supported by the low NH 4 + concentrations found in this study.…”
Section: Grazing Effects On Soil and Plant Parametersmentioning
confidence: 99%